Hydration behaviors, knowledge, and attitudes among Chinese recreational marathon runners: a cross-sectional study - Zhang, Jingyi; Chen, Yan; Zhao, Xueyuan; Li, Xiangxin; Wen, Wei; Wu, Wenqiang; Zou, Menghui; Qiu, Junqiang (Frontiers in Nutrition, 2025)
ObjectivesThis cross-sectional study aimed to assess fluid replenishment behaviors, knowledge, and attitudes among Chinese recreational marathon runners and to inform future health education strategies regarding optimal hydration.DesignThe survey was conducted between January and December 2024. Based on previously validated questionnaires, the instrument was adapted and administered to assess hydration behaviors, knowledge, and attitudes among marathon participants in major road races across China. A total of 461 valid responses were collected, including 357 male participants (38.9 ± 9.3 years) and 104 female participants (39.5 ± 8.9 years), representing a range of athletic performance levels. The response rate was 94.9%. Data were analyzed using IBM SPSS 27.0 and Microsoft Excel.ResultOver 70% of runners (72.5%) failed to meet recommended daily fluid intake standards (p < 0.001). Over half (57.7%) consumed 150 mL of fluid before the race, mainly plain water before (68.1%) and sports drinks during (56.6%) and after (54.0%) the race. Participants primarily obtained hydration knowledge from friends/family (54.9%) and social media (45.6%). Most participants (93.7%) acknowledged water’s health benefits and were willing (92.2%) to improve hydration habits to enhance athletic performance (p < 0.001 for all). Hydration knowledge varied by gender, age, and training level. Participants better understood pre- and mid-exercise hydration and the concept that thirst indicates existing dehydration. However, only 21.5% knew the recommended daily intake (1500–1700 ml), 39.9% understood the differences among mineral, spring, and purified water, and 46.8% recognized the need for post-exercise rehydration.ConclusionThese findings indicate that over half of recreational marathon runners are at risk of dehydration, highlighting that a lack of knowledge poses a dilemma for some runners who fall into a dehydrated state. This underscores the need for targeted education and awareness programs on scientific hydration knowledge and attitudes among recreational marathon runners to improve their health and athletic performance.